Pemberdayaan masyarakat dalam deteksi tuberkulosis secara mandiri di Kelurahan Sukamaju, Palembang, Sumatera Selatan - Sudarto, Sudarto; Fathurrachman, Alif; Indira, Dwi; Pasaribu, Rouly; Andriani, Linda; Rasyid, Ahmad; Ahmad, Zen (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Pulmonary tuberculosis (TB) is a long-recognized airway infection. However, the elimination of TB cases is still a major problem worldwide, especially Indonesia. According to the world tuberculosis report in 2023, Indonesia ranks 2nd in the world with an estimated 1,060,000 cases. The number of pulmonary tuberculosis cases found and reported in Indonesia still has not reached the national target. Case finding efforts are a joint effort of the government, health workers and the community. Bad stigma about pulmonary TB is still a challenge in the community. Therefore, community empowerment is needed in TB case finding efforts through independent TB detection that can be easily done by the community, so that they are able to recognize the symptoms of pulmonary TB for themselves and people in their neighborhood. Through community service activities by providing information through counseling materials about pulmonary TB detection efforts in the community. Through questionnaires before and after counseling, an increase in understanding of the discovery of pulmonary tuberculosis cases independently was obtained, with a mean score before 40 points and a mean score after counseling of 100 points. This is expected to increase the number of pulmonary TB case finding in Palembang city.